Rice cake ileus - Osamu Imataki; Makiko Uemura (Clinical Case Reports, 2024)
Key Clinical Message Japanese rice cake, mochi, is made from glutinous rice, a very sticky food. Mochi is a popular preserved food during the New Year holiday celebration. However, mochi can be hazardous because of lethal choking or ileus.